2011
DOI: 10.1007/s12039-011-0108-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bismuth carboxylates—synthesis and characterization of a new structural form of bismuth(III) dipicolinate

Abstract: Synthesis and X-ray structure of a new bismuth dipicolinate cooordination polymer, {[Bi((2,6-O 2 C) 2 C 5 H 3 N)((2-HO 2 C-6-O 2 C)C 5 H 3 N)(H 2 O)] 2 .5H 2 O} n (7) are presented. Compound 7 has dimeric units with a Bi 2 O 2 skeleton that are linked by additional weak Bi-O interactions leading to a polymeric structure. The overall coordination number at bismuth is 9 [two Bi-N and seven Bi-O bonds]. New routes to a second crystalline modification (4 ) of the previously reported coordination polymer, bismuth t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…The Bi-O bond lengths are in the range 2.2637(29)-2.8281(27) Å and the Bi-N bond lengths are in the range 2.4324(15)-2.6665(15) Å (table 2). The average values of Bi-O and Bi-N bond lengths are comparable with the corresponding ones reported in the literature for relatedbismuth(III) complexes with pyridine-2,6-dicarboxylate or 4-hydroxy pyridine-2,6-dicarboxylate[12,[15][16][17][18]35,36,[45][46][47][48][49][50][51].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…The Bi-O bond lengths are in the range 2.2637(29)-2.8281(27) Å and the Bi-N bond lengths are in the range 2.4324(15)-2.6665(15) Å (table 2). The average values of Bi-O and Bi-N bond lengths are comparable with the corresponding ones reported in the literature for relatedbismuth(III) complexes with pyridine-2,6-dicarboxylate or 4-hydroxy pyridine-2,6-dicarboxylate[12,[15][16][17][18]35,36,[45][46][47][48][49][50][51].…”
supporting
confidence: 86%
“…Bismuth-based materials have many potential applications in the field of photoluminescence, medicine, catalysis and piezoelectric or high dielectric constant materials [33][34][35][36][37][38][39][40][41][42][43][44]. A large number of bismuth(III) carboxylates are clinically active against Helicobacter pylori and other gastrointestinal disorders [35,44].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of the acidic Bi(III) ion with ligands bearing N-O donor atoms produced a wide selection of pharmaceutically active complexes (e.g., complex 24), which have been extensively used for the treatment of a broad spectrum of gastrointestinal disorders. The derivatives of dipicolinic acid have produced interesting motifs that exhibit relatively good stabilities in aqueous environments and high solubilities in slightly acidic conditions (Anjaneyulu et al 2010(Anjaneyulu et al , 2011.…”
Section: Bismuthmentioning
confidence: 99%
“…Nevertheless, there is a growing interest in coordination polymers containing bismuth as is demonstrated by a number of more recent publications. Most examples of such coordination polymers reported to date are based on carboxylates (Stavila et al, 2004;Chen et al, 2008Chen et al, , 2011Jiang et al, 2008;Andrews et al, 2009;Thirumurugan et al, 2010;Anjaneyulu and Swamy, 2011;Wibowo et al, 2011;Anjaneyulu et al, 2012) and nitrogen-containing donor ligands (Morsali, 2006;Morsali and Mahjoub, 2006;Tershansy et al, 2007). Additionally, poly meric bismuth alkoxides (Whitmire et al, 1992;Roggan et al, 2005;Kricheldorf et al, 2008;Breunig et al, 2009b) have been reported as well as coordination polymers with sulfur-or seleniumcontaining donor ligands (Barton et al, 2000;Yim et al, 2000;Briand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%